Effectiveness of Constructivist Methods of Science Learning at Secondary Schools in Nepal - Shrestha, Laxman; Acharya, Kamal Prasad (Innovative Research Journal, 2024)
This paper explores the prominence of student-centered (constructivist) method over teacher-centered (lecture) method in public schools in Nepal. A quantitative research relying on experimental design was carried. Simple random sampling technique was employed to select the schools and the participants for the research. Students were randomly selected from the Kathmandu district, were grouped as experimental and control. The study was carried in 30 students of each school. Experimental group was taught by using constructivist method and control group was with traditional method. The pretest- post test design were administered to both the groups .The arithmetic mean, variance and standard deviation were calculated for data analysis. It is found that students’ achievement level of experimental groups were far better than control group. Constructivist method of learning was effective in comparison with the traditional lecturing in learning science. It is recommended that the concerned authorities especially Nepal Government and Curriculum Development Center would use it in framing curriculum development and accentuation on prioritizing the constructivist method of teaching and learning.